Red blood cells stored for increasing periods produce progressive impairments in nitric oxide–mediated vasodilation - Alexander, Jason T. (2013)
BACKGROUND: Clinical outcomes in transfused patients may be affected by the duration of blood storage, possibly due to red blood cell (RBC)-mediated disruption of nitric oxide (NO) signaling, a key regulator of vascular tone and blood flow. STUDY DESIGN AND METHODS: AS-1 RBC units stored up to 42 days were sampled at selected storage times. Samples were added to aortic rings ex vivo, a system where NO-mediated vasodilation could be experimentally controlled. RESULTS: RBC units showed storage-dependent changes in plasma hemoglobin (Hb), RBC 2,3-diphosphoglycerate acid, and RBC adenosine triphosphate conforming to expected profiles. When freshly collected (Day 0) blood was added to rat aortic rings, methacholine (MCh) stimulated substantial NO-mediated vasodilation. In contrast, MCh produced no vasodilation in the presence of blood stored for 42 days. Surprisingly, the vasoinhibitory effects of stored RBCs were almost totally mediated by RBCs themselves: removal of the supernatant did not attenuate the inhibitory effects, while addition of supernatant alone to the aortic rings only minimally inhibited MCh-stimulated relaxation. Stored RBCs did not inhibit vasodilation by a direct NO donor, demonstrating that the RBC-mediated vasoinhibitory mechanism did not work by NO scavenging. CONCLUSIONS: These studies have revealed a previously unrecognized vasoinhibitory activity of stored RBCs, which is more potent than the described effects of free Hb and works through a different mechanism that does not involve NO scavenging but may function by reducing endothelial NO production. Through this novel mechanism, transfusion of small volumes of stored blood may be able to disrupt physiologic vasodilatory responses and thereby possibly cause adverse clinical outcomes.